GENDER REPRODUCTION IN GENDER ARCHETYPED CHILDREN PICTURE BOOK - Lingga Manesha Samantha, - (2010)
This research entitled "Gender Reproduction In Gender Archetyped Children Picture Book" is aimed at investigating the reproduction of gender archetyped children picture books of pre-school children through their drawings and how gender ideology in children's picture books place children as gendered subjects through the gender archetyped characters. The research employs descriptive analysis, which is qualitative in nature and uses visual grammar as the theoretical framework. Based on the analysis, the research found that children use their cultural values and experiences to reproduce gender archetyped picture books. These are manifested through the choosing of colors, the shapes and attributes used by the represented participants, and the compositions in their drawings. The research also found that gender ideology placed children as gendered subjects through the represented participants they draw. Their drawings indicate their cultural values and their everyday experiences, such as the differences of roles and statuses between female and male represented participants. Further, their cultural values and their experiences are manifested in the choosing in the given of main represented participant who had more power to control other represented participants.